A biomarker-enriched, randomized phase II trial of Adavosertib (AZD1775) plus Paclitaxel and Carboplatin for women with Platinum-sensitive TP53-mutant Ovarian Cancer - Oza, Amit M.; Estevez-Diz, Maria; Grischke, Eva-Maria; Hall, Marcia; Marmé, Frederik; Provencher, Diane; Uyar, Denise; Weberpals, Johanne I.; Wenham, Robert M.; Laing, Naomi; Tracy, Michael; Freshwater, Tomoko; et al. (Clinical cancer research, 2020)
Preclinical studies show that adavosertib, a WEE1 kinase inhibitor, sensitizes TP53-mutant cells to chemotherapy. We hypothesized that adavosertib, plus chemotherapy, would enhance efficacy versus placebo in TP53-mutated ovarian cancer.Following safety run-in, this double-blind phase II trial (NCT01357161) randomized women with TP53-mutated, platinum-sensitive ovarian cancer to oral adavosertib (225 mg twice daily for 2.5 days/21-day cycle) or placebo, plus carboplatin (AUC5) and paclitaxel (175 mg/m2), until disease progression or for six cycles. The primary endpoints were progression-free survival (PFS) by enhanced RECIST v1.1 [ePFS (volumetric)] and safety. Secondary/exploratory objectives included PFS by RECIST v1.1 (single dimension), objective response rate, overall survival, and analysis of tumor gene profile versus sensitivity to adavosertib.A total of 121 patients were randomized to adavosertib (A+C; n = 59) and placebo (P+C; n = 62) plus chemotherapy. Adding adavosertib to chemotherapy improved ePFS [median, 7.9 (95% confidence interval (CI), 6.9-9.9) vs. 7.3 months (5.6-8.2); HR 0.63 (95% CI, 0.38-1.06); two-sided P = 0.080], meeting the predefined significance threshold (P < 0.2). Clinical benefit was observed following A+C for patients with different TP53 mutation subtypes, identifying possible response biomarkers. An increase in adverse events was seen with A+C versus P+C: greatest for diarrhea (adavosertib 75%; placebo 37%), vomiting (63%; 27%), anemia (53%; 32%), and all grade ≥3 adverse events (78%; 65%).Establishing an optimal strategy for managing tolerability and identifying specific patient populations most likely to benefit from treatment may increase clinical benefit. Future studies should consider additional adavosertib doses within the chemotherapy treatment cycle and the potential for maintenance therapy.
Gesehen am 26.09.2025